Analysis & Design of E-Community Development System in Jakarta, Indonesia - Idananta, Kanyadian; Mayliana, Mayliana (Politeknik Harapan Bersama, 2018)
Nowadays, community service becoming essentials in education, but these activities are done manually, as each institution had to find communities and sponsors before opening a class. To support these activities we are analyzing and designing an E-Community Development system to help communities, institutions and also lecturers in completing their responsibilities. Using this system, all registered communities, institutions and lecturers in Indonesia can communicate with each other using a web-based system. We hope the presence of this application can cut down the process of opening a community service class. The method used in analyzing and designing the system are by problem identification, literature study, goal specification, data collection, analysis and data interpretation, and evaluation and report.